Estudo do potencial anticâncer de novos derivados acridínicos sintéticos em modelos experimentais in vitro - Barros, Francisco Washington Araújo (2010)
Acridines are planar aromatic polycyclic molecules that have the ability to progress in nuclear DNA. Many of its representatives have antibacterial, antiparasitic and antitumor. This study evaluated the cytotoxic potential of 22 new acridine compounds in strains of human tumor cells. Among these, four compounds [5-(acridin-9-yl-methilene)-3-(4-methyl-benzyl)-thiazolidine-2,4-dione, AC4; 5-(acridin-9-yl-methilene)-3-(4-bromine-benzyl)-thiazolidine-2,4-dione, AC7; 5-(acridin-9-yl-methilene)-3-(4-chloro-benzyl)-thiazolidine-2,4-dione, AC10; and 5-(acridin-9-yl-methilene)-3-(4-fluor-benzyl)-thiazolidine-2,4-dione, AC23] were active, especially in HCT-8 (colon) and SF-296 (glioblastoma), with IC50 values ranging from 2.3 to 5.3 mg / mL. The compounds were selective for tumor cells, provided they do not inhibit (IC50 > 25 µg/mL) cell proliferation monocucleares human peripheral blood (CMSPH) and were not able to induce DNA damage to these cells. None of the compounds showed hemolytic activity against erythrocytes of mice (EC50 > 200 µg/mL), suggesting a cytotoxicity by more specific mechanisms. In order to determine the mechanism involved in the selective cytotoxicity of compounds was carried out a sequence of in vitro experiments, using the line HCT-8 as a model. The cells were treated in different concentrations of compounds (2.5, 5 and 10 µg/mL) for 12 and 24 hours. All compounds were able to reduce the viability test (trypan blue) and proliferation (BrdU assay) of HCT-8 cells after treatment. Induction of apoptosis by acridine derivatives was determined by flow cytometry (membrane integrity, DNA fragmentation and internucleosomal transmembrane potential) and morphological analysis of cellular changes (ethidium bromide/acridine orange, and hematoxylin-eosin). The analysis by flow cytometry showed that the compounds evaluated promoted mitochondrial depolarization, which shows the activation of apoptosis by intrinsic pathway in HCT-8 cells. In the analysis of screening in 3 different mutant strains of Saccharomyces cerevisiae, it was observed that the line Top1Δ (without topoisomerase I) showed resistance to acridine compounds tested at a concentration of 50 µg/mL. In addition, the acridines partially inhibited the relaxation of DNA by topoisomerase I, suggesting that the compounds AC4, AC7, AC10, AC23 has the potential antiproliferative partly related to inhibition of catalytic activity of this enzyme. These data indicate the potential anticancer compounds tested.